SO034A NEW MARKER OF RESISTANT HYPERTENSION IN CKD PATIENTS. (6th June 2020) - Gembillo, Guido; Siligato, Rossella; Cernaro, Valeria; Satta, Ersilia; Conti, Giovanni; Salvo, Antonino; Romeo, Adolfo; Calabrese, Vincenzo; Sposito, Giovanna; Ferlazzo, Guido; Santoro, Domenico
Abstract: Background and Aims: Monocytes -HDL ratio (MHR), has emerged as a possible marker of inflammation and oxidative stress (OS), demonstrating its possible use in the population with Chronic Kidney Disease (CKD). These effects seem to be modulated by an increased lipid production, by reduced cellular catabolism of fatty acids and by the alteration of the antioxidant, anti-inflammatory mechanisms and the reverse cholesterol transport of HDL. The latter to exert favorable effects on inflammatory and oxidative pathway. The purpose of our research is to evaluate the link between MHR and resistant hypertension (RH) which, together with inflammation, OS and atherosclerosis, represents a widespread feature in the population with CKD and carries a greater risk of premature death due to cardiovascular disease. Method: A retrospective study has been performed on 251 hypertensive patients, admitted in the last 6 months to the Unit of Nephrology and Dialysis of the Policlinic G. Martino of Messina, Italy. 80 patients were diagnosed with RH, defined as blood pressure that remains above 140/90 mmHg despite use of three different classes of antihypertensive medications (one of which must be a diuretic) at the maximum tolerated doses. We evaluated the distribution of data with Kolmogorov-Smirnov test and, considering that MHR had a non-normal distribution, we expressed the values as medians and interquartile ranges (IQR). Moreover, differences between groups with Mann-Whitney test, correlations with Rank Correlation and Spearman's Rho coefficient were also considered in the analysis. Finally, we assessed the differences of variables between the means of different groups with ANOVA test using multiple regression to valuate independent relations between variables. Results: MHR appeared to be positively correlated with serum creatinine levels (ρ=0.24; P=0.0001) (Figure 1). MHR correlated with the number of antihypertensive drugs per patient in the entire cohort of patients (F = 18.23; P <0.001) (Figure 2). Patients with RH had a significantly higher MHR than patients without resistant hypertension (0.1493 [IQR 0.12 - 0.18] versus 0.11 [IQR 0.0 - 0.13], P <0.0001) (Figure 3). Conclusion: MHR has proven to be an accurate tool in quantifying inflammatory status and OS, whose effectiveness lies in the close correlation that exists between HDL and monocytes. HDL prevent and reverse the recruitment of monocytes in the arterial wall and their activation through a decrease in their F-actin content, thereby reducing the expression of CD11b on monocytes, and modulating their adhesion to the endothelium. Our study showed that MHR could be a useful and immediate tool to evaluate OS and inflammatory status in order to select high-risk patients and identify earlier and appropriate treatment strategies.